Tomographic evaluation of lower second molars with type C configuration in an imaging center in Lima - Arévalo Híjar, Olga (2024)
The lower second molar mostly has a C configuration and it is important to know the internal anatomy and classification to have a better clinical approach, so the objective was to evaluate the prevalence and types of C-shaped canals in permanent mandibular second molars by using cone beam computed tomography (CBCT).. Materials and Methods: 150 CTHC images of mandibular second molars were used. The following was recorded: sex, presence of C-shaped canal, location, morphology and type of C configuration according to Fan’s classification, which is divided into C1, C2, C3 (c and d), C4 and C5. The chi- square test was used to analyze the differences between groups (p˂0.05, considered a statistically significant difference). Results: Of the 300 teeth evaluated, 12.6% had C-shaped canals. There were no statistically significant differences between C-shaped canals and sex. This configuration tends to appear bilaterally, however, when it appears unilaterally, we find it mostly on the right. At the level of the pulp chamber floor and middle third, C1 was the most frequent and at the apical level it was C4 for both parts (37 and 47). Conclusions: The prevalence of C-shaped canals is not high. Bilateral appearance is more common than unilateral. Fan’s classification is a complement to Melton’s, since it will help us understand in more detail the morphological changes of this configuration along the root.